2021
DOI: 10.1186/s13073-021-00948-1
|View full text |Cite
|
Sign up to set email alerts
|

An epigenetic and transcriptomic signature of immune tolerance in human monocytes through multi-omics integration

Abstract: Background The plasticity of monocytes enables them to exert multiple roles during an immune response, including promoting immune tolerance. How monocytes alter their functions to convey immune tolerance in the context of lower respiratory tract infections in humans is not well understood. Here, we sought to identify epigenetic and transcriptomic features of cytokine production capacity in circulating monocytes during community-acquired pneumonia (CAP). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…Although non-referring to the entire study population, transcriptomic data indicated that genes involved in cholesterol biosynthesis were altered in clarithromycin-treated patients, relative to placebo, at study day 5. Other data also indicate the presence of an axis between cholesterol synthesis, antigen presentation and monocyte reprogramming toward a trained immunity phenotype [ 25 27 ]. Whether this axis is modulated by clarithromycin remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Although non-referring to the entire study population, transcriptomic data indicated that genes involved in cholesterol biosynthesis were altered in clarithromycin-treated patients, relative to placebo, at study day 5. Other data also indicate the presence of an axis between cholesterol synthesis, antigen presentation and monocyte reprogramming toward a trained immunity phenotype [ 25 27 ]. Whether this axis is modulated by clarithromycin remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, CD14 + monocytes and polymorphonuclear leukocytes (PMNs) were obtained from patients with CAP at both timepoints and stimulated ex vivo for 24 h (monocytes) or 2 h (PMNs) with lipopolysaccharide (LPS) or heat-killed K. pneumoniae . Following stimulation, we measured a wide array of monocyte-derived cytokines and neutrophil-derived cytokines and degranulation products by multiplex assay ( STAR methods and previously reported by our group ( Brands et al., 2021 )). Of note, we observed no differences in leukocyte, lymphocyte, or neutrophil counts between clusters ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For transcriptional RNA profiling of monocytes, patients with previously diagnosed malignant hematological disease, or exposed to chemotherapy, systemic corticosteroids and/or other immunosuppressive drugs were excluded ( Brands et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 b). It has been shown that there was an association between cholesterol biosynthesis and impaired monocytes cytokine production in the context of human lower respiratory tract infections [ 74 ]. It is worth noting that all three cell types showed disturbance of the phospholipid metabolic process after METH treatment (Fig.…”
Section: Discussionmentioning
confidence: 99%